Nasopharyngolaryngoscopy in Upper Airway Disorders among the Patients Visiting Tertiary Hospital: A Retrospective Review of Clinical Findings and Diagnosis - Gurung, Lal Bahadur; Gurung, Sarita; Bhandari, Ramesh; Aryal, Bivek; Bajracharya, Rohita; Kandel, Damodar; Parajuli, Ramesh (Journal of Bharatpur Hospital, 2025)
Background Flexible Nasopharyngolaryngoscopy (NPL) is minimally invasive diagnostic procedure done with the use of a flexible endoscope to examine anatomical and pathological changes in the nasal cavity, pharynx and larynx. Many patients visit ENT OPD with upper airway problems with clinical features like nasal obstruction, throat discomfort, change in voice, difficulty in swallowing etc. This study aims to assess the nasopharyngolaryngoscopic findings in patients presenting with upper airway disorders. MethodsThis is a single center, retrospective, descriptive cross-sectional study conducted among 720 patients who underwent NPL for various upper airway problems in Department of ENT & HNS, Bharatpur Hospital, Chitwan from 1st Jan 2024 April to 31st Dec 2024. Ethical approval from IRC of Bharatpur Hospital (Ref No. 081/82-076). Results720 patients between age group of six to ninety years were studied. Female (473) outnumbered male (247) with ratio 1:0.52. Majority of the patients (268, 37.2%) presented with complaint of foreign body sensation in throat. NPL findings was normal in majority of patients (n=197, 27.4%), followed by Laryngopharyngeal reflux (126, 17.5%). Benign lesions like polyp, nodule, cyst were common in larynx in comparison to malignant lesion. Deviated nasal septum was also common among the patients (77, 10.7%). Conclusions NPL is a cost-effective brief procedure which is helpful to find out the affected site causing upper airway disorder even though findings can be normal in some of the cases. Flexible NPL examination can be performed in patients without any delay for early diagnosis of pathology in nose, pharynx and larynx.